THE SIGNIFICANCE OF ECHINOCOCCOSIS IN VETERINARY MEDICINE AND HUMAN LIFE - Kamalova A.I., (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides information on the history, prevalence, veterinary and human significance of echinococcosis, as well as preventive measures.